2014
DOI: 10.1371/journal.pone.0103358
|View full text |Cite
|
Sign up to set email alerts
|

Native Rodent Species Are Unlikely Sources of Infection for Leishmania (Viannia) braziliensis along the Transoceanic Highway in Madre de Dios, Peru

Abstract: An estimated 2.3 million disability-adjusted life years are lost globally from leishmaniasis. In Peru's Amazon region, the department of Madre de Dios (MDD) rises above the rest of the country in terms of the annual incidence rates of human leishmaniasis. Leishmania (Viannia) braziliensis is the species most frequently responsible for the form of disease that results in tissue destruction of the nose and mouth. However, essentially nothing is known regarding the reservoirs of this vector-borne, zoonotic parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(61 reference statements)
0
5
1
Order By: Relevance
“…Neitzke-Abreu et al (2013) tested the accuracy of some PCR-based techniques for CL diagnosis in humans and concluded that the use of blood (buffy coat) may be indicated for patients with no lesions. Our prevalence was higher than reported in other Brazilian (CÁSSIA-PIRES et al, 2014;LARA-SILVA et al, 2014) and foreign studies (LIMA et al, 2002;PAPADOGIANNAKIS et al, 2010;MENDONÇA et al, 2011;SHENDER et al, 2014;VLADIMIR et al, 2015). One study analyzed rodents from waste sites (VLADIMIR et al, 2015) in Croatia; 1/173 (0.5%) rodent (R. rattus) tested positive for L. (L.) infantum; the authors identified five species of phlebotomine sand flies at those places.…”
Section: Discussioncontrasting
confidence: 50%
“…Neitzke-Abreu et al (2013) tested the accuracy of some PCR-based techniques for CL diagnosis in humans and concluded that the use of blood (buffy coat) may be indicated for patients with no lesions. Our prevalence was higher than reported in other Brazilian (CÁSSIA-PIRES et al, 2014;LARA-SILVA et al, 2014) and foreign studies (LIMA et al, 2002;PAPADOGIANNAKIS et al, 2010;MENDONÇA et al, 2011;SHENDER et al, 2014;VLADIMIR et al, 2015). One study analyzed rodents from waste sites (VLADIMIR et al, 2015) in Croatia; 1/173 (0.5%) rodent (R. rattus) tested positive for L. (L.) infantum; the authors identified five species of phlebotomine sand flies at those places.…”
Section: Discussioncontrasting
confidence: 50%
“…guyanensis [ 5 , 11 13 ]. However, information about Leishmania vectors, reservoirs, their role in disease transmission and the variables influencing their distribution is still limited [ 14 – 16 ]. For instance, a surveillance study using molecular methods for parasite identification, failed to detect Leishmania on more than 80 wild native rodents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…During 1984–1994, this rate increased to 12.69–40.02 people per 100,000 inhabitants, before showing a slight drop and stabilizing during the years 1994–1996 with a mortality rate of approximately 32.45 people per 100,000 inhabitants (Escalante, 1997). One of the zones with the highest rates of annual mortality is, as previously mentioned, Madre de Dios (Shender et al, 2014).…”
Section: Introductionmentioning
confidence: 92%